Gastrointestinal symptoms in autism spectrum disorder: A review of the literature on ascertainment and prevalence - Holingue, Calliope; Newill, Carol; Lee, Li-Ching; Pasricha, Pankaj J; Daniele Fallin, M (Autism research, 2018)
There is no standard approach to measuring GI symptoms in individuals with ASD, despite postulated interactions. The objectives of this study were to (a) describe the range of GI symptom ascertainment approaches in studies of ASD, (b) describe the range of prevalence estimates across studies, and (c) assess associations between ascertainment approach and prevalence estimates. Studies published from 1/1/1980 to 1/31/2017 were collected via PubMed. Eligibility included studies with at least ten individuals with ASD that measured GI symptoms or conditions. We excluded review and hypothesis papers. We extracted information on study design, GI symptom ascertainment method, demographics, and ASD diagnostic criteria. From a subset of studies, we extracted GI symptom estimates. Out of a possible 386 titles, 144 were included. The prevalence range for constipation was 4.3-45.5% (median 22%), for diarrhea was 2.3-75.6% (median 13.0%), and for any or more than one symptom was 4.2-96.8% (median 46.8%). GI symptoms differed significantly by age of individuals, primary goal of study, study design, study sample, and who reported symptoms (P < .05). Due to small sample size, we were not able to test for associations between every GI symptom and study characteristic of interest, or examine associations between GI symptoms and intellectual or verbal disability. Studies used a broad range of methods to ascertain GI symptoms in ASD. GI symptoms varied widely across these studies, with significant differences by study characteristics. Our findings highlight the need for a reliable, valid GI assessment tool to be used consistently across studies of ASD. Autism Res 2018, 11: 24-36. © 2017 International Society for Autism Research, Wiley Periodicals, Inc. We reviewed studies having to do with autism spectrum disorder and the gastrointestinal system, dating back to 1980. We found that the median prevalence of constipation was 22.2%, diarrhea 13.0%, and any symptom 46.8%. All symptoms had a wide range of estimates across studies. GI symptoms were associated with characteristics of the study, including who measured the GI symptoms. We call for the development of a reliable and valid GI questionnaire for studies of ASD.